نظام التحكيم التجاري في حسم منازعات الأوراق المالية: دراسة مقارنة - حمو، نسيبة إبراهيم; الناصري، مصطفى ناطق صالح مطلوب (جامعة كركوك - كلية القانون والعلوم السياسية, 2016)
A Commercial Arbitration Become major role in the resolution of many trade disputes, and because of the advantages and developments successive which have been adopted in the resolution of disputes, securities markets, through the development of a private suit capital markets rules and the nature of their disputes, and varied countries in the extent of Arbitration considered the best way to resolve such disputes, or resorting to eliminate normal, but the existence of the arbitration to impose himself in this area through the attention of States to provide efficient and professional expertise in the field of financial markets to reassure customers and investors in the market for the existence of a specialized point of resolving their disputes away from the courts.
أصبح للتحكيم التجاري دورا كبير في حسم العديد من المنازعات التجارية، وبسبب المزايا والتطورات المتلاحقة فيه فلقد تم اعتماده في مجال فض منازعات أسواق الأوراق المالية، من خلال وضع قواعد خاصة تلائم أسواق المال وطبيعة منازعاتها، وتباينت الدول في مدي اعتبار التحكيم الوسيلة الأمثل لحسم مثل هذه المنازعات، أو اللجوء للقضاء العادي، ألا أن وجود التحكيم فرض نفسه في هذا المجال من خلال اهتمام الدول بتوفير الخبرات الكفوءة والمهنية في مجال الأسواق المالية ليطمئن المتعاملين والمستثمرين في السوق لوجود جهة متخصصة بحسم منازعاتهم بعيد عن القضاء.
Keywords: القوانين والتشريعات -- التحكيم التجاري -- الاوراق المالية -- فض المنازعات -- المنازعات التجارية